The Concept of Justice in Polygamy and Its Implications for Islamic Family Education - Wardiah Hamid (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study examines the practice of polygamy through a critical interpretation of the Qur'an by analyzing the relationship between the normative permission contained in Surah An-Nisa verse 3 and the ethical limitation emphasized in verse 129. Polygamy remains one of the most debated issues in contemporary Islamic studies because it stands at the intersection of textual legitimacy, gender justice, and changing social realities. Previous studies have generally approached polygamy from either normative jurisprudence or sociological perspectives, while relatively few have integrated Qur'anic exegesis, historical context, and the objectives of Islamic law (maqasid al-shariah) into a single analytical framework. This research employs a qualitative library research approach using critical Qur'anic interpretation, contextual analysis, and maqasid al-shariah as complementary analytical perspectives. Primary data were obtained from Qur'anic verses, classical and contemporary tafsir literature, and major works on Islamic legal thought, while secondary data were collected from scholarly books and peer-reviewed journal articles discussing Islamic family law, gender studies, and Qur'anic hermeneutics. The findings indicate that the Qur'anic permission for polygamy should not be understood as a universal norm but rather as a contextual social regulation intended to protect vulnerable members of society under particular historical circumstances. Furthermore, the study demonstrates that the Qur'an establishes justice as the central ethical requirement for polygamy while simultaneously acknowledging the human inability to achieve perfect justice, particularly in emotional relationships. Consequently, the ethical orientation of the Qur'an encourages a more restrictive understanding of polygamy consistent with justice, human dignity, and public welfare.